Membrane biofilm communities in full-scale membrane bioreactors are not randomly assembled and consist of a core microbiome. (15th October 2017) - Matar, Gerald K.; Bagchi, Samik; Zhang, Kai; Oerther, Daniel B.; Saikaly, Pascal E.
Abstract: Finding efficient biofouling control strategies requires a better understanding of the microbial ecology of membrane biofilm communities in membrane bioreactors (MBRs). Studies that characterized the membrane biofilm communities in lab-and pilot-scale MBRs are numerous, yet similar studies in full-scale MBRs are limited. Also, most of these studies have characterized the mature biofilm communities with very few studies addressing early biofilm communities. In this study, five full-scale MBRs located in Seattle (Washington, U.S.A.) were selected to address two questions concerning membrane biofilm communities (early and mature): (i) Is the assembly of biofilm communities (early and mature) the result of random immigration of species from the source community (i.e. activated sludge)? and (ii) Is there a core membrane biofilm community in full-scale MBRs? Membrane biofilm (early and mature) and activated sludge (AS) samples were collected from the five MBRs, and 16S rRNA gene sequencing was applied to investigate the bacterial communities of AS and membrane biofilms (early and mature). Alpha and beta diversity measures revealed clear differences in the bacterial community structure between the AS and biofilm (early and mature) samples in the five full-scale MBRs. These differences were mainly due to the presence of large number of unique but rare operational taxonomic units (∼13% of total reads in each MBR) in each sample. In contrast, a high percentage (∼87% of total reads in each MBR) of sequence reads was shared between AS and biofilm samples in each MBR, and these shared sequence reads mainly belong to the dominant taxa in these samples. Despite the large fraction of shared sequence reads between AS and biofilm samples, simulated biofilm communities from random sampling of the respective AS community revealed that biofilm communities differed significantly from the random assemblages (P < 0.001 for each MBR), indicating that the biofilm communities (early and mature) are unlikely to represent a random sample of the AS community. In addition to the presence of unique operational taxonomic units in each biofilm sample (early or mature), comparative analysis of operational taxonomic units and genera revealed the presence of a core biofilm community in the five full-scale MBRs. These findings provided insight into the membrane biofilm communities in full-scale MBRs. More comparative studies are needed in the future to elucidate the factors shaping the core and unique biofilm communities in full-scale MBRs. Graphical abstract: Image 1 Highlights: Membrane biofilm (early and mature) community analysis in five full-scale MBRs. Clear difference in bacterial community diversity between AS and biofilm communities. This difference was attributed to the presence of large number of unique but rare taxa in each sample. Membrane biofilm (early and mature) communities are not randomly assembled from AS community. A core membrane biofilm community exists in full-scale MBRs.